Association between dietary betaine intake and overweight or obesity - Maierheba Kuerbanjiang; Wenzhuo Yu; Ting Shang; Yuchen Liu; Dina Muheyati; Mei-Xia Lv; Muhairemu Jielili; Jia Han (Scientific Reports)
Abstract Betaine exhibits significant physiological functions in organisms and has positive impacts on obesity, alcohol-induced and metabolic-associated liver disease, diabetes, cardiovascular diseases, and certain cancers. However, the evidence from epidemiological studies is limited and inconsistent. This study aimed to investigate the association between dietary betaine intake and the incidence of overweight or obesity. A total of 492 subjects from a dietary survey were equally classified into four groups (Q1, Q2, Q3, and Q4) according to the quartiles of dietary betaine intake and further investigate the correlation of betaine intake with body weight, body mass index (BMI), waist circumference (WC), hip circumference (HC), waist-to-hip ratio (WHR), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), fasting blood glucose (FBG), fasting insulin (FINS), homeostasis model assessment of insulin resistance (Homa-IR), systolic blood pressure (SBP), and diastolic blood pressure (DBP). The study subjects were further divided into normal-weight and overweight/obesity groups to compare the differences in obesity-related indices and betaine intake between the normal-weight and overweight/obesity individuals. The association between dietary betaine intake and the presence of overweight/obesity was performed by logistic regression. The results indicated that a higher betaine intake was correlated with a lower BMI and HC. And higher intake of calorie and macronutrients, as well as food species like cereals, meats, tubers, fruits, vegetables, nuts, and seeds, were also associated with an increased betaine intake. Cereals, being a main food source of betaine, provided more than 85% of betaine in the daily diet. Furthermore, subjects with normal weight had a higher dietary betaine intake than those with overweight/obesity. Logistic regression showed that the highest quartile (Q4) of betaine intake was associated with a lower incidence of overweight/obesity risk. In conclusion, cereals were the main food source of dietary betaine intake. There was a significant difference in dietary betaine intake between normal weight and overweight/obese individuals. Importantly, the highest betaine intake was associated with a lower risk of overweight/obesity.